Investigating the effect of G-Bond and Z-PRIME Plus on the bond strength between prefabricated zirconia posts and the canal wall (in in vitro conditions) - Ezzatollah Jalalian; Nahid Darvish; Sogol Saberi (Tabriz University of Medical Sciences, 2018)
Purpose: The aim of this study is to analyze the effect of G-Bond and Z-PRIME Plus on the bond strength between prefabricated zirconia posts and the canal wall. Material and Method: The study was carried out on 21 premolar teeth with similar conditions. The collected samples were cut at the CEJ. After root canal treatment of the roots, the post space was prepared with a length of 10mm. The samples were randomly allocated into two groups of 10. G-bond was used in one group and Z-PRIME plus in the other to prepare the posts' surface. After cementation and mounting the samples in polyester, the post was cut from the apical area into three equal sections. The bond strength of the samples was tested using the push out on a universal testing machine. The acquired data was analyzed using the T-Test. Results: The average for the control group was 14.3N, the G-bond group had an average of 27.6±11.8N and the Z-PRIME plus group's average was 27.4±13.4N. There is no statistically significant relationship between the two groups (P<0.9). Both methods of surface treatment increased bond strength. The bond strength in different sections such as coronal, middle and apical for each group is different. Conclusion: There is no statistically significant relationship between the G-bond and Z-prime plus groups and both products increase the bond strength of prefabricated zirconia posts.